Marketing Strategy for the Song "Tell Me" by Saladdays - Iqbal Ahdalino, Mahatma (Repertoar, 2025)
This research aims to describe the arrangement of the song "Tell Me" and how Saladday's marketing strategy was carried out in marketing the song "Tell Me." This research uses a descriptive qualitative approach to identify and answer problem formulations related to arrangement data and marketing strategies. The data analyzed is the song "Tell Me". Researchers perform data analysis techniques: data reduction, data presentation, and conclusion drawing. This research results in the song "Tell Me" using C# Major tonality with allegro tempo and 4/4 time. The harmony or chords used are extended chords, where there are no triadicelements, and there is only harmony with four or more notes giving rise to chords 7, 9, 11, or 13. The overall musical structure of this song is Intro - Verse 1 - Pre Chorus - Chorus - Interlude - Verse 2 - Chorus - Coda. Then, the chord progression in the central theme of this song is IV - V - VI - V - I. Furthermore, the marketing strategies applied by Saladdays are distribution on the Spotify and Apple Music streaming platforms, pre-release campaigns, distribution on the YouTube platform, and live performances.